Viability test of ethanol extract of beluntas (pluchea indica) leaves on In vitro fibroblast cells - Rani Wulan Sari; Natallia Pranata; Vinna Kurniawati Sugiaman (Wolters Kluwer Medknow Publications, 2019)
Background: Tooth extraction is the most frequently conducted dental care procedure. In Indonesia, there is an extremely high utilization of dental and oral health services for tooth extraction, reaching 79.6%. Pain is a side effect of extraction. Pain due to extraction wounds can be treated with analgesic drugs, but alternative drugs with minimal or no side effects are still being researched. An herbal active beluntas leaf substance can reduce pain from extraction wounds. The beluntas plant not only aids in healing wounds but also exhibits anti-inflammatory and antipyretic effects. Objectives: In this study, the aims were to determine the 50% inhibitory concentration (IC50value) and examine the viability effect of an ethanol extract of beluntas leaves on fibroblast cell cultures in vitro. Methods: Laboratory experiments were carried out. Beluntas leaves were obtained; their leaf extracts were prepared using ethanol as the solvent; phytochemical tests were performed. Triplicate measurements for the viability of 3T3 BALB/c fibroblast cells were carried out using the Methylthiazol sulfophenyl (MTS Assay) method. The extract concentrations were 500, 250, 125, 62.50, 31.25, 15.63, and 7.81 μg/mL. Results: Data analysis was carried out by one-way analysis of variance statistical test. Analysis results revealed that extract concentrations of 500, 31.25, 15.63, and 7.81 μg/mL exhibit a significant difference in the effect of cytotoxicity (P < 0.05) on fibroblast cells, and the IC50value is 265.388 μg/mL. Conclusion: A significant difference in the cytotoxicity effect between the concentrations of the ethanol extract of beluntas (P. indica) leaves on the fibroblast cell cultures in vitro was observed. The beluntas leaf extract at an IC50value of 7.81 μg/mL did not affect cell viability; hence, it is considered safe.